2017
DOI: 10.1037/cdp0000145
|View full text |Cite
|
Sign up to set email alerts
|

Not your model minority: Own-group activism among Asian Americans.

Abstract: In addition to replicating broad findings from the collective action literature among Asian Americans, this research highlights the importance of contextualized group-based beliefs about inequality (model minority beliefs) for understanding engagement among racial minority groups. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 59 publications
11
80
0
Order By: Relevance
“…In fact, correlational work has shown that endorsement of underlying structural factors driving inequality across a range of dimensions has been linked with decreased system justifying ideology and increased support of promoting diversity and disrupting prejudice (Curtin, Stewart, & Cole, 2015). Structural awareness is predicted in part by past experiences with discrimination and has been showed to indirectly predict activism to benefit the ingroup among Asian Americans by decreasing model minority beliefs (an individual, meritocratic outlook) and increasing a sense of collective identity (Tran & Curtin, 2017). In fact, structural explanations for inequality are a common theme in activist reports of motivations for collective action (Curtin, Kende, & Kende, 2016), suggesting a link between structural thinking about inequality and action for social change.…”
Section: Structural Attributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, correlational work has shown that endorsement of underlying structural factors driving inequality across a range of dimensions has been linked with decreased system justifying ideology and increased support of promoting diversity and disrupting prejudice (Curtin, Stewart, & Cole, 2015). Structural awareness is predicted in part by past experiences with discrimination and has been showed to indirectly predict activism to benefit the ingroup among Asian Americans by decreasing model minority beliefs (an individual, meritocratic outlook) and increasing a sense of collective identity (Tran & Curtin, 2017). In fact, structural explanations for inequality are a common theme in activist reports of motivations for collective action (Curtin, Kende, & Kende, 2016), suggesting a link between structural thinking about inequality and action for social change.…”
Section: Structural Attributionsmentioning
confidence: 99%
“…The role of structural thinking among marginalized groups appears in the literatures on stratum and group consciousness, which explore the consequences of recognizing one's ingroup's low-power position in society, evaluating the legitimacy of this position, and endorsing collective action to address the situation (Gurin et al, 1980). This theory has later been defined as structural awareness and collective identity, and suggested to directly predict activism and mediate the effect of personal experiences on activism (Duncan, 2012;Tran & Curtin, 2017). Surprisingly, group consciousness has not been widely applied to the intraminority context.…”
Section: Structural Attributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They must cope with the resulting lack of control, certainty, security, and loss of connections with mainstream society (Jost et al, 2008). Therefore, a necessary prerequisite to adopting a system-challenging ideology is structural awareness-the attribution of inequality and injustice to social structures rather than individual ability (Curtin et al, 2015;Martorana et al, 2005;Tran & Curtin, 2017). Studies have found that structural awareness mediates the relationship between experiences of discrimination and participation in collective action (Duncan, 1999;Tran & Curtin, 2017).…”
Section: System Justification and Structural Awarenessmentioning
confidence: 99%
“…Therefore, a necessary prerequisite to adopting a system-challenging ideology is structural awareness-the attribution of inequality and injustice to social structures rather than individual ability (Curtin et al, 2015;Martorana et al, 2005;Tran & Curtin, 2017). Studies have found that structural awareness mediates the relationship between experiences of discrimination and participation in collective action (Duncan, 1999;Tran & Curtin, 2017). Furthermore, when individuals act collectively for social change, they express not only structural awareness but structural reimagination.…”
Section: System Justification and Structural Awarenessmentioning
confidence: 99%